O arquiteto e o processo de projeto participativo - Sibele Meyer Lana (2007)
The current situation of the popular dwelling is revealed as chaotic. And the solution of the habitation deficit goes far beyond the dwellings supply; It is linked to the habitability concept. New cities administration models are being proposed, as the so called participative-environmental, where the popular participation in the decisive processes is now the key element. The same should occur in the social interest project processes.This paper aims at discussing the role developed by the architect in this new way of projecting, how the relations among professionals and the final customer occur and what changes in the way of projecting. From the identified problems, hypotheses are created to be investigated afterall we are curious beings. The first (hypothesis) is just that the nowledgemultiplicity demanded from the architect is greater and possesses a higher interdisciplinary level; besides the compliance degree of the same with the final product goes beyond the customers satisfaction. As a second hypothesis, there is no doubt that Paulo Freire´s pedagogy can assist make the participative process results stronger. The research is accomplished through the study of case of the Residential Project Serra Verde RSV and the qualitative research, developed through the participative observation and interviews with the RSV community members. For the conclusions presentation, the observations and the obtained results will be compared with the hypotheses and the studied reality. Although the popular participation in the project process has not been totally effected, it can be deemed that, without any doubt, there has been a significant gain in the final product. Suggestions for new studies and researches will, then, be made. After all, only shared knowledge is valid knowledge (Paulo Freire).